IMPLEMENTATION OF BUSINESS MODEL CANVAS IN CHEMICAL MANUFACTURING COMPANY PT TIMURAYA TUNGGAL - Mangiring Siburian, Agus (Dinasti International Journal of Economics, Finance & Accounting, 2020)
One of the industries that drives the economy is manufacturing. Companies to be able to continue to excel and compete need a business model that is in line with the strategy to achieve corporate goals, especially under the current conditions of economic globalization. Business Model Canvas (BMC) is one of the business models that describes how a company creates, delivers and records the value of the product or service it produces. The background of this research is to identify the business model used by chemical manufacturing companies in creating value for their customers. The aim of this study is to find out how the implementation of BMC in chemical manufacturing companies in creating value and provide advice and recommendations on the business models used. Key activities and key resources are important elements in a chemical company's business model, since the production process is the main activity in the manufacture of products, which are then sold and distributed to customers